The relationship between language difficulties, psychosocial difficulties and speech–language pathology service access in the community. Issue 2 (23rd February 2021) - Trembath, David; Conti‐Ramsden, Gina; Xie, Gang; Cook, Fallon; Reilly, Sheena
Abstract: Background: A range of factors may impact whether children access speech–language pathology (SLP) services, beyond their communication difficulties. For instance, co‐occurring psychosocial difficulties may amplify children's observable difficulties, leading to greater access. It is important to examine such associations because they may reflect inherent differences between children with language difficulties who access services and those who do not, indicating under‐servicing for subgroups in the community. Aims: The first aim was to examine possible differences in psychosocial difficulties between children with language difficulties who did versus did not access SLP services in the past 12 months. The second aim was to examine the unique contribution of psychosocial difficulties to service access, over and above language difficulties and other common predictors of service access. Methods & Procedures: Analyses were carried out on data gathered from 808 eleven‐year‐old children who took part in the Early Language in Victoria Study (ELVS). Children were categorized as having language difficulties based on their CELF‐4 Core Language Score with a cut‐point of > 1.25 SD below the mean. The primary outcome measure was access to SLP services in the past 12 months. Comparison and predictor variables included children's psychosocial difficulties, language skills, relevant demographic variables (gender, caregiver education) and prior SLP access. Outcomes & Results: A total of 42 children with language difficulties who had accessed SLP services had significantly greater psychosocial difficulties than those who had not (SDQ Total Difficulties, U = 53.00, z = –4.080, p < 0.001). Using binary logistic regression, a model examining child gender, caregiver education, psychosocial difficulties (internalizing and externalizing behaviours), language difficulties and prior SLP access (in earlier years) was significant χ 2 (8) = 137.285, p < 0.001, with increased externalizing difficulties (OR = 1.213, p < 0.001), increased communication difficulties (OR = 0.949, p < 0.001), and prior SLP access (OR = 7.430, p < 0.001) identified as unique predictors of service access. Conclusions & Implications: The results indicate that children with language difficulties who have comorbid psychosocial difficulties are more likely to access services than those who do not. Accordingly, children with language difficulties who access clinical services may require interdisciplinary support, while children without co‐morbid psychosocial difficulties may be under‐referred for SLP services. What this paper adds What is already known on this subject: There is evidence that a range of personal and contextual factors impact the likelihood of a person accessing healthcare services beyond the specific issue of concern. What this paper adds to existing knowledge: In this population‐based study, we provide statistical evidence that children with language difficulties who had higher levels of psychosocial difficulties were more likely to access SLP services than those who had lower levels. What are the potential or actual clinical implications of this work?: Children with language difficulties who access SLP services may require support for psychosocial difficulties, while children who do not have comorbid difficulties may be underserviced in the community.